Monitoring tunnel liners using fiber optic sensors - Duan, Ting Lin (Nanyang Technological University, 2022)
Monitoring tunnel lining performance plays a significant role during the construction and maintenance period. It provides important information for assessing the condition of tunnel segments on time to ensure the safe operation of tunnels. Over the years, steel fiber reinforced concrete (SFRC) has been increasingly used for tunnelling in Singapore. Meanwhile, Fiber Bragg Gratings (FBG) sensors have been widely used to collect data for structural health monitoring. However, FBG is a kind of point-sensing system, which has limitations to show the tunnel segment’s deformation trends. To solve this problem, Chirped Fiber Bragg Gratings (CFBG) and Distributed Fiber Optic Sensing (DFOS) are used as monitor systems in this project, while limited research has been conducted in this area. This report presents part of the work done under the Cites of Tomorrow project using FBG, CFBG, and DFOS as embedded fiber optic sensors to investigate and monitor the performance of SFRC liners from casting to installation. A two-layer monitor system for the SFRC segments has been designed and loading tests have been conducted to check the performance of SFRC segments under various loads. Based on the test results, it is concluded that the fiber-optic sensor system offers a great prospect for monitoring the tunnel lining. Moreover, the test results provide a deep understanding of the SFRC performance at various stages from casting to loading.